GC–MS Untargeted Analysis of Volatile Compounds in Four Red Grape Varieties (Vitis vinifera L. cv) at Different Maturity Stages near Harvest - Xiaobo Gu; Xue Zhang; Keqing Wang; Xi Lv; Ruyi Li; Wen Ma (Foods, 2022)
Grape volatile compounds directly determine the aroma quality of wines. Although the aroma profile of grapes evolved greatly at different maturity stages, there were less considerations for aroma status when determining grape harvest time. In the present study, several maturation indicators, namely, sugars/acids ratio, free volatile compounds, bound volatile compounds and IBMP (3-isobutyl-2-methoxypyrazine) content were monitored in four red wine grape varieties (Vitis vinifera L. cv Cabernet Sauvignon, Cabernet Gernischet, Cabernet Franc and Merlot) near harvest time (42 days) in Ningxia, China. The results showed that the highest sugars/acids ratio was reached on day 21 and day 28 for Merlot and the other three varieties, respectively. For both free and bound volatile compounds, the content of carbonyl compounds decreased continuously in the process of ripening. The contents of free alcohols, esters and terpenes increased in the ripening stage and decreased in the stage of over-ripening. The accumulation of favorable bound aroma compounds peaked at day 35. The content of IBMP presenting a green smell in all four varieties descended continuously and kept steady from day 28. Therefore, the present findings revealed that the best aroma maturity time of four studied grape varieties was later than the sugars/acids ratio in Ningxia region. Aroma maturity should be taken into account during harvest time determination.